Recent Updates of DNA Incorporated in Carbon Nanotubes and Nanoparticles for Electrochemical Sensors and Biosensors - Yogeswaran, Umasankar (Molecular Diversity Preservation International (MDPI), 2008)
Innovations in the field of electrochemical sensors and biosensors are of much importance nowadays. These devices are designed with probes and micro electrodes. The miniaturized designs of these sensors allow analyses of materials without damaging the samples. Some of these sensors are also useful for real time analysis within the host system, so these sensors are considered to be more advantageous than other types of sensors. The active sensing materials used in these types of sensors can be any material that acts as a catalyst for the oxidation or reduction of particular analyte or set of analytes. Among various kinds of sensing materials, deoxyribonucleic acid (DNA), carbon nanotubes (CNTs) and nanoparticles have received considerable attraction in recent years. DNA is one of the classes of natural polymers, which can interact with CNTs and nanoparticles to form new types of composite materials. These composite materials have also been used as sensing materials for sensor applications. They have advantages in characteristics such as extraordinary low weight and multifunctional properties. In this article, advantages of DNA incorporated in CNT and nanoparticle hybrids for electrochemical sensors and biosensors are presented in detail, along with some key results noted from the literature.